Exposure to Bisphenol A and phthalates metabolites in the third trimester of pregnancy and BMI trajectories. Issue 9 (26th April 2018) - Yang, T. C.; Peterson, K. E.; Meeker, J. D.; Sánchez, B. N.; Zhang, Z.; Cantoral, A.; Solano, M.; Tellez‐Rojo, M. M.
Summary: Background: Bisphenol A (BPA) and phthalates metabolites are linked to a variety of adverse health consequences but studies have not explored their association with growth trajectories. Objective: Explore body mass index (BMI) trajectories for tertile exposures to BPA and phthalates metabolites in the third trimester of pregnancy. Methods: We constructed BMI (kg/m 2 ) trajectories from birth to 14 years in a birth cohort of 249 children from Mexico City using tertiles of third trimester maternal urinary concentrations of BPA and phthalates metabolites. Fractional age polynomials and mixed effects models were fit separately by sex. Predicted models were plotted for each metabolite tertile with the covariates mother's education and BMI centered at average values. Results: Highest predicted BMI trajectories for female children were observed for third tertile exposure to the phthalate metabolite mono(2‐ethyl‐5‐carboxypentyl) phthalate. In male children, first tertile exposure to mono‐isobutyl phthalate and monobenzyl phthalate and second tertile exposure to mono(2‐ethylhexyl) phthalate and mono(2‐ethyl‐5‐hydroxyhexyl) phthalate predicted the highest BMI trajectory by adolescence. There was no relationshsip between BPA and child growth trajectory. Conclusions: These results suggest sex‐specific differences in BMI trajectories by levels of metabolite exposure. Additional studies are needed to consider growth through adolescence in assessing the association of pregnancy exposures on child's BMI.